2010
DOI: 10.1007/s11104-010-0523-y
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic biofortification of Brassica with selenium—enrichment of SeMet and its identification in Brassica seeds and meal

Abstract: Selenium (Se) is an essential micronutrient and is circulated to the food chain through crops. Brassica species are efficient in Se accumulation and thus, good species for Se biofortification purposes. The residual fraction obtained after oil processing of Brassica seeds, the meal, is an important protein source in animal diets and used in feed concentrates. The accumulation of soil or foliar applied Se in the seeds and meal of Brassica napus and B. rapa as well as its effects on growth and yield formation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 31 publications
(41 reference statements)
7
38
0
Order By: Relevance
“…In this study, we can clearly note that selenite could promote purple lettuce growth at low concentrations, but purple lettuce growth was inhibited at high concentrations (exceeding 8 μM) as compared with the control (Figs 1 and 2). With the increase of selenite concentration in the nutrient solution, Se content in agricultural plants significantly increased, which agrees with those previous results [23][24][25].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we can clearly note that selenite could promote purple lettuce growth at low concentrations, but purple lettuce growth was inhibited at high concentrations (exceeding 8 μM) as compared with the control (Figs 1 and 2). With the increase of selenite concentration in the nutrient solution, Se content in agricultural plants significantly increased, which agrees with those previous results [23][24][25].…”
Section: Discussionsupporting
confidence: 93%
“…Two-year average results of selenite foliar applications at the growth stage of 2 nd node on the main stem (32 BBCH) showed no significant effect on winter wheat grain yields, while selenate supply (10 g Se/ha) resulted in a significant increase of grain yield (Table 2) (Broadley et al 2010), yield of rapeseed (Seppänen et al 2010) and maize grain yield (Chilimba et al 2012, Wang et al 2013. However, several studies showed that Se application positively affected the plant.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is increasing evidence that Se enrichment of plants can exert beneficial effects on their growth, antioxidant capacity and stress tolerance (Hartikainen 2005), Se however has not been recognised as an essential micronutrient for higher plants (Seppänen et al 2010). This paper reports the comparative effects of selenite and selenate on the lettuce plants, with a special focus on the use of this species for biofortification with Se.…”
Section: Discussionmentioning
confidence: 99%